6x+2(5x+12)=25-2(1-8x)

Simple and best practice solution for 6x+2(5x+12)=25-2(1-8x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+2(5x+12)=25-2(1-8x) equation:


Simplifying
6x + 2(5x + 12) = 25 + -2(1 + -8x)

Reorder the terms:
6x + 2(12 + 5x) = 25 + -2(1 + -8x)
6x + (12 * 2 + 5x * 2) = 25 + -2(1 + -8x)
6x + (24 + 10x) = 25 + -2(1 + -8x)

Reorder the terms:
24 + 6x + 10x = 25 + -2(1 + -8x)

Combine like terms: 6x + 10x = 16x
24 + 16x = 25 + -2(1 + -8x)
24 + 16x = 25 + (1 * -2 + -8x * -2)
24 + 16x = 25 + (-2 + 16x)

Combine like terms: 25 + -2 = 23
24 + 16x = 23 + 16x

Add '-16x' to each side of the equation.
24 + 16x + -16x = 23 + 16x + -16x

Combine like terms: 16x + -16x = 0
24 + 0 = 23 + 16x + -16x
24 = 23 + 16x + -16x

Combine like terms: 16x + -16x = 0
24 = 23 + 0
24 = 23

Solving
24 = 23

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 16-2t=3/2t | | X+.20x+35=89 | | 25.20x+20=71 | | 2n+6n=72 | | 25.20x+0.20=71 | | 7x-21=7(x-4)+7 | | 42x=-64 | | a^2b-b^3= | | (9k-2)2=0 | | 17x-7=0 | | (21y-1)+(4x+23)+(9x-38)=180 | | 2y^3/4h^2(2y^1/3h^-4)^6 | | 4x-10=x-1 | | -(3z+2x)= | | 85-3=49 | | a^2-12a+26=-6 | | -7=13+.4b | | (10-t)(10+r)=0 | | 8/3c-2=2/3c=12 | | -28m-12=88 | | 0.09xX=61.67 | | P(w)=5w^2-9w+9 | | 3.3q-5.7-3.4q=-2.1q-5.2 | | 7x+(x+20)= | | x-8-12=5 | | (4-s)(4-s)=0 | | 5m^2+28m+32=0 | | x+12-18=26 | | 5m^2+28+32=0 | | -6=-6+0.6y | | 2(x-22)+3=2x-1 | | -6=-6+0.6 |

Equations solver categories